MENINGKATKAN POSISI TAWAR KELUARGA SEBAGAI KONSUMEN DALAM MENGHADAPI KRISIS EKONOMI - Sri Wening, Sri Wening (Jurnal Cakrawala Pendidikan, 2016)
?he plunln~ctting economy experienced by Indonesians in the last few months have raised difficulties for almost all fa~niliesa s consumers, though the lcvei of difficulty may vary. In [he ongoing economic crisis, every family's buying power of course decreases bccause the income of the family rem;~ins unchanged while the price of basic necessities conllnues to skyrocket. There are actually families having enough funds but they cannot get the goods needed because they are not found in the market. In such a condition, the power control of every fanlily over each fanlily menlber is h~ghlyn eeded to determine the attitude in the lamily. ?he fa~nily as consumers must inevitably conduct self- introspection to sce whethcr they havc becn consumers with a highly critical and inclcpcndcot bargaining positioil. 'lherelore, certain efforts must be made in the fact t)I the econonlic crisis in order to maintain the quality the famjly's standards of living for the interest of the family. One of thc efforts that can be made lor the purpose of improving the bargaining position of the family is by improving the quality of' communication in the family, cultivating the consuming awarenes of the family, and also maintaining the presence of' behavioral examples partaining to the bargaining position fro111 the mother or the father.